Precision and repeatability analysis of a motion analysis system for traction therapy - Jin Park, Se; Subramaniyam, Murali; Nam Min, Seung; Eun Kim, Seoung; Kim, Sikyung (International Journal of Engineering and Technology, 2018)
Neck pain or cervical pain is most common in individuals who are all working in seated postures for prolonged period of time, example computer users. The pain caused by extreme postural positions including forward head postures and extension angle maintained in cervical. The use of cervical vertebra traction therapy has increased as a part of rehabilitation medicine. However, lack of usability standard in this traction therapy i.e., the exact instructions on how to choose the traction force and location are unclear. To fix this issue, first, the cervical spine traction system analysing the change of cervical spine depending on the traction location has been investigated. Motion analysis systems are widely used to measure the changes in the body part movement. However, the precision and repeatability of motion analysis systems are not much studied. In this paper, the precision and repeatability of a three-dimensional (3D) motion analysis system (i.e., NDI’s Optotrak Certus (OC)) is evaluated with developed 3D robot for traction therapy as an application example. The 3D robot quantitated the accuracy and precision of the system regarding angle and distance. Angle and distance among markers showed good agreement between measurements, and comparable measures of precision reported. Experimental results demonstrate a measure of precision and repeatability for the movement of the patients on the cervical traction system; hence the repeatability was satisfactory.
Keywords: Medical Device; Extension Therapy; Rehabilitation; Cervical Spine.